2015
DOI: 10.1016/j.ijhydene.2014.11.051
|View full text |Cite
|
Sign up to set email alerts
|

The effects of compression on single and multiphase flow in a model polymer electrolyte membrane fuel cell gas diffusion layer

Abstract: A two-dimensional study of an idealised fibrous medium representing the gas diffusion layer of a PEMFC is conducted using computational fluid dynamics. Beginning with an isotropic case the medium is compressed uni-directionally to observe the effects on single and multiphase flow. Relations between the compression ratio and the permeability of the medium are deduced and key parameters dictating the changes in flow are elucidated. The main conclusions are that whilst compression reduces the absolute permeabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…The Voronoi graph has been used by several pore network modelers as a proxy for a random fibrous medium [21,49,50]. With this approach the edges of the Voronoi graph represent fibers, the Voronoi cells define pores, and the facets between cells are the throat constrictions.…”
Section: A Voronoi Cellsmentioning
confidence: 99%
“…The Voronoi graph has been used by several pore network modelers as a proxy for a random fibrous medium [21,49,50]. With this approach the edges of the Voronoi graph represent fibers, the Voronoi cells define pores, and the facets between cells are the throat constrictions.…”
Section: A Voronoi Cellsmentioning
confidence: 99%
“…In operating fuel cells the percolating pathways offer less resistance to fluid flow as less pressure is required to inflate a droplet interface growing in the fuel cell gas channels than to invade smaller pores inside the GDL. Therefore, once a pathway is established the breakthrough pattern is often repeated and liquid droplets can be seen forming at the same positions over and over, as modeled by Tranter et al 1, and observed experimentally by Quesnel et al 33. Saturation at breakthrough is therefore a good indication of average medium saturation during fuel cell operation.…”
Section: Model Developmentmentioning
confidence: 80%
“…A summary of the experimental and numerical studies of the various effects of compression on the GDL can be found in our previous work 1. In general, the effective transport properties (permeability and diffusivity) of the GDL are decreased with compression due to the reduced pore volume and connectivity, while electrical and thermal conductivity increase as contact resistance is reduced.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, several investigations about liquid water removal from various homogenously and non‐homogenously compressed GDLs have been conducted , . However, to the best of authors' knowledge, water is considered as a continuous stream in all of these mentioned investigations.…”
Section: Introductionmentioning
confidence: 99%